Exploring affecting factors of and developing a framework for teachers' online instruction. (December 2022) - Xue, Sijia; Wang, Chuang; Yang, Yanchao
Abstract: Online teaching has been capitalized to maintain normal educational activities since the outset of the pandemic. However, the wide adoption of emergency remote teaching may present challenges to teachers in terms of performing their instructional work. Hence, this study aimed to deeply explore the affecting factors of teachers' adoption of online instruction during emergencies through a qualitative research design. Semi-structured interviews and document analysis were utilized to collect data with nine higher education teachers at nine Chinese universities. Eight categories of factors emerged from this study that influenced the participants' adoption of online instruction, namely, facilitating conditions, technology self-efficacy, characteristics of learners, teaching administration, pedagogical factors, resistance to change, time issues, and security issues. A framework for developing teachers' competencies for online instruction is proposed based on the results. Highlights: A qualitative research design is used to explore teacher technology acceptance. The original Technology Acceptance Model has been extended. A framework for enhancing teachers' abilities for online instruction is developed.